2016
DOI: 10.1111/hiv.12441
|View full text |Cite
|
Sign up to set email alerts
|

Ageing with HIV: do comorbidities and polymedication drive treatment optimization?

Abstract: In ageing HIV-infected patients, especially those with a long history of HIV infection, comorbidities and coprescriptions are highly prevalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…As summarized in Table 1, commonly observed comorbidities which may contribute to the issue of polypharmacy in ageing PLWH are hypertension, dyslipidaemia, diabetes mellitus, kidney disease, cardiovascular disease, respiratory disorders, bone disorders or cancer. Of interest, several studies have reported a higher prevalence of comorbidities in PLWH compared to age-matched uninfected individuals [5,[19][20][21][22][23][24][25][26][27]. Furthermore, multimorbidity defined by the concurrent presence of ≥2 comorbidities has been shown to be significantly higher in PLWH compared to uninfected controls, particularly in those with a long history of HIV infection [5,19,25].…”
Section: Comorbidities Among Hiv-positive Individualsmentioning
confidence: 99%
“…As summarized in Table 1, commonly observed comorbidities which may contribute to the issue of polypharmacy in ageing PLWH are hypertension, dyslipidaemia, diabetes mellitus, kidney disease, cardiovascular disease, respiratory disorders, bone disorders or cancer. Of interest, several studies have reported a higher prevalence of comorbidities in PLWH compared to age-matched uninfected individuals [5,[19][20][21][22][23][24][25][26][27]. Furthermore, multimorbidity defined by the concurrent presence of ≥2 comorbidities has been shown to be significantly higher in PLWH compared to uninfected controls, particularly in those with a long history of HIV infection [5,19,25].…”
Section: Comorbidities Among Hiv-positive Individualsmentioning
confidence: 99%
“…Even with adequate treatment, about 10% of patients had detectable VL and TCD4 + lymphocyte count below 500 cells/mm3 (43%). As the aging of people living with HIV/AIDS has been poorly studied and most randomized studies do not include older adults, it is not known for sure what would be the most appropriate therapeutic scheme, taking into account the physiological changes of aging, the frequent use of several medications for chronic comorbidities and treatment adherence 9,17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…The score presented here could be useful when assessing individual risk-benefit ratios, by improving the accuracy of mortality risk assessment, or to define populations that may benefit the most from intervention. Such a score may reflect the extra burden of multimorbidity and polypharmacy in the aged PLHIV population [ 2 , 30 ] and could be associated with frailty measures [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%